Uso da vacina cepa rugosa RB51 contra brucelose em fêmeas bovinas gestantes em diferentes estágios de gestação - Barbosa, Adriana Agostini (2014)
Field strains of Brucella abortus, as well as the vaccines made of antigens from portions of S19 lipopolysaccharides (LPS), induce the same specific antibody, what makes very difficult to distinguish by means of serologic tests vaccinated animals and those infected. To avoid serologic interference with diagnosis it is used a vaccine that does not induce O-lipopolysaccharide (O-LPS) antibodies, that is, a rough strain that does not induce agglutinating antibodies. A Brucella abortus strain that does not induce agglutinating antibodies was isolated in the 80 s and, when used as a vaccine, offers protection without interfering with usual serologic methods, even in adult cows. Some works indicate that the rough strain is safe when inoculated in pregnant females, but only when reduced dose as used. The use of normal doses in pregnant cows is not recommended, what leads to potential failures of immunization programs. Literature information does not allow for stating if such vaccine at normal doses is safe when administrated to pregnant cows. The aim of this study was to evaluate the safety of a full dose vaccine made of a rough strain (1.0-3.4 × 1010 colony forming units - CFU) (Brucelina Rebeccin Vallée Brazil) in pregnant cows at different stages of pregnancy. The study was conducted in the state of Minas Gerais, Brazil. The experiment used 96 female bovines of mixed breed (Bos taurus x Bos indicus), nulliparous and multiparous, at three different pregnancy stages (initial stage: TI, middle stage: TC, and final stage: TF), randomly assigned to two groups (treated and control T or C), composed of 6 treatments with 16 animals. After vaccine administration, the animals were kept together on brachiaria grass pastures with mineral supplementation. The following variables werw compared using X2 test of the following variables: Percentage of calves born, percentage of live calves 60 days after delivery and number of seropositive cows and calves during such period. A 5% chance was deemed as significant. No differences were seen between treatments in each period or when periods were analyzed all together for the percentage of calves born alive and healthy (87.5; 87.5; 93.8; 93.8. 81.3 and 100%) or for the calves alive 60 days after delivery (75.0; 87.5; 87.5; 87.5. 81.3 and 93.8%) - p>0.05 for TI-C, TM-C, TF-C, TI-T, TM-T and TF-T, respectively). No animal was found to be seropositive in the usual detection tests (fast seroagglutination) at 60 days of age. It was concluded that the administration of vaccine Brucelina Rebeccin at any pregnancy stage is safe for bovine females, since it does not lead to fetal losses nor interferes with calves feasibility after birth. Additionally, the use of such product in the vaccination of pregnant cows does not lead to the formation of antibodies that can be detected by the usual diagnostic tests for brucellosis in calves and cows